CAD and document of inspection jig for an automotive part - Mohd. Salleh, Farrahshaida (2009)
Jig has widely used in various applications such as in inspection, machining, assembly and fabrication works. Some cases jig developmental works take more than a year to complete especially in automotive and aerospace industries where precision and safety are prime important. In most applications in small and medium scale industries, the jig design works are done manually and based on trial and error basis. This results in losses in production time and cost. With the development of computer and information technology, the design work can be simplified and the whole fabrication process can be shortened. In this project, Unigraphic software was utilized to document the design procedure and facilitate the whole jig design and assembly process via parametric part library concept. The spreadsheet function within Unigraphic software was used to parameterize all the common parts in jig application. Three case studies were used in developing the design procedure which includes two inspection and one machining jigs. The proposed procedure was written in the sequential order according to the norm of jig design procedure being practiced in small and medium scale industries. In order to design a jig, the designer has to follow the steps in the proposed procedure and match with the parametric part library database which has been developed using Unigraphic software environment. The effectiveness of the proposed procedure and parametric parts library created in the Unigraphic software were evaluated using two different jigs for machining and inspecting a motorcycle oil pump body. It is found that the proposed procedure and parametric part library concept works well for designing and assembling these two jigs.